Nurse practitioners in home health care: an update - Neal‐Boylan, Leslie; Mager, Diana; Kazer, Meredith Wallace (Home Health Care Management & Practice, 2012)
Nurse practitioners are playing an increasingly visible role in home care. The Institute of Medicine in collaboration with the Robert Wood Johnson Foundation recommends wider use of Advanced Practice Registered Nurses and there has been growing interest in using the role in home care.1 However, the physician remains the provider who must sign home health agency paperwork and orders. The "Home Health Care Planning Improvement Act" would allow nurse practitioners to certify Medicare-sponsored treatment plans.2 This article will discuss the status of the nurse practitioner role in home care, the impact of reimbursement on home care services, how the passage of the new act would change current practice, and a vision for the future role of the nurse practitioner in home health care. © 2012 SAGE Publications.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00276 tex.type: [object Object]
Keywords: Home Health Care Improvement Act; conceptual model; dept.nur; home health care; nurse practitioner; transitional care model